Germination potential of Dasylirion spp. as response to pre-germination thermal regimes: Germination potential of Dasylirion spp. - Ortiz-López, Adriana; Velasco-Velasco, Vicente Arturo; Martínez-Gutiérrez, Gabino Alberto; Campos-Angeles, Gisela Virginia; Rodríguez-Ortiz, Gerardo (Ecosistemas y Recursos Agropecuarios, 2024)
The Dasylirion genus is of economic, environmental and cultural importance. Its main form of reproduction is sexual; however, the seeds present exogenous dormancy, which hinders their proliferation and reduces the natural population. This study aimed to evaluate the germination potential of Dasylirion spp. in response to different thermal regimes applied to fruits under laboratory conditions. A directed sampling was carried out to collect inflorescences in San Andrés Lagunas and San Jerónimo, Villa de Tamazulapam in 2022, and a composite sample of fruits from Asunción Nochixtlán in 2021, these localities belonging to the Oaxacan Mixtec region. Reproductive indicators of the seeds were measured. Statistical analyses were performed on germination data in a completely randomized design with factorial arrangement (3 collection sites, 3 temperatures-time and 3 methods of heat application), analysis of variance, Duncan's comparison of means (P ≤ 0.05) and regression models. San Jeronimo seeds showed significantly higher weight (5.28 g), purity (88 %), viability (70 %) and humidity (10 %); likewise, they significantly surpassed San Andres and Nochixtlán in germination speed, germination speed index and germination percentage. In the San Jeronimo sample, the treatment with heat in an oven at 58 °C for 4 minutes obtained 96% germination after 15 days. In addition, it was observed that temperatures of 40 °C and 58 °C weakened the physical structure and mechanical resistance of the cover, which facilitated its removal.
Keywords: Cucharilla; germinative energy; latency; pericarp; sotol